Popularity Melalui Track Record Di Panggung Politik - Aldianto, Andrean; Noak, Piers Andreas; Mahaswari Jayanthi Mertha, Anak Agung Sagung Mirah (Jurnal Nawala Politika; 2021: Jurnal Ilmu Politik 2021, 2021)
This study aims to determine how someone who has participated in a national talent search event, namely Puteri Bali and Miss Indonesia, then becomes a public figure (influencer) and becomes a political actor. This research is framed by using the Sociometric Popularity theory by AL Freedman, seeing that the Princess Bali label (dropout) is very influential in popularity so that it benefits her electability on the political stage. The research method used is descriptive qualitative method using primary data and secondary data, because it describes and describes Yunita Oktarini as a political actor. The results of the research are: first, Yunita Oktarini uses her title as Putri Bali to increase her electability in society. Second, mutualism symbiosis, which is mutual benefit between Yunita and political parties. Third, the inner circle is a supporting factor and support for mass organizations obtained from their proximity to the party elite.   Keywords : Popularity Sociometric, People Power , Relatives Relationship, Electability